Examining The Effects of Widowhood Rites Practices: A Case Study Among The People of Talensi and Nabdam In The Upper East Region of Ghana - Ba–an, Maxwell Tengolzor; Segbefia, Samuel Kwabla; Ofori, Maxwell (South Asian Journal of Social Sciences and Humanities, 2022)
Some practices are barbaric, atrocious, backward, immoral, commoditization and an abusive violation of the sexual and human rights of the powerless. Widowhood rites are performed at the fresh funeral and during the final funeral rites. Widows prefer to be inherited by their grandsons so that they are free to choose a man of their choice and still hold on to their deceased husband assets. The Talensi widow would strangle a goat and part of the skin is used to cover the private of the dead for burial. The Nabdams would slaughter a sheep and an elder will slaughter it. In both cases older women served as the enforcers and custodians of such practices. The purpose of this study was to examine widowhood rites practices among the people of Talensi and Nabdam in the Upper East Region of Ghana. The study employed ethnography research method. Purposive sampling technique was used to sample twenty (20) widows from Talensi and Nabdam. The study recommended that Ghana's widows need to lead in the reporting of violations of their rights to the appropriate state institutions responsible and follow up to ensure justice is delivered. Non-governmental Organizations and Community-based organizations which are advocating for the abolition of widowhood rites should collaborate with traditional authorities to modify the practices.
Keywords: Widow; widowhood rites; Talensi; Nabdam; Abusive Volation